A case study of the mining exploration in Barangay Paglaum, Tacloban City. - Caliste, Rochelle T. (Tacloban City Rochelle Caliste, 2011)
Brgy. Paglaum is one of the barangays of Tacloban City, Leyte. It was chosen as the research locale of this study.
The study employed a self-administered interview questionnaires used in soliciting opinions and reactions served as an instrument for the study. The researchers utilized an interview schedule in gathering the needed data
Resullts revealed that the only ongoing mining exploration in Tacloban City is only in Brgy. Paglaum. And it was proven by the records of Department of Environment and Natural Resouces (Mining and Geosciences Bureau) and MIning Tenements Managemnt Division.
Results of this study is significant because it will give insights regarding the views and opinions of the City government of Tacloban, some officials of DENR and course the residents of the affected barangay. Morever, this may help in uplifting the citizen's participation.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science